Use Spatial Analysis Tools in A Study The Hydromorphological Characteristics of Wadi Al-Rimah in Its Lower Section in Qassim Area - Alenziy, Maha Awwad; Aldughairi, Ahmed Abdullah (Journal of natural sciences, life and applied sciences, 2023)
The torrent and floods represent one of the most dangerous, natural catastrophe. It is caused by the dry valise and semidry. It shows Its effects when it is attacked for housing, farming or services all the same. The river’s network for the lowest Al-Rimah valley in Qassim region in the middle of the kingdom of Saudi Arabia. It is one of the oldest hydrology network which was formed because of the climatic systems during the late quad. These river networks have witnessed allot of high floods which flooded Qassim region during the dry Holocene period. In Almaeish age appeared in the horizon some indications for some flood models which warns an environmental crises. In case it isn’t cured and understanding of its old environment. The apply of the radar technique like Shuttle Radar Topography Mission and the techniques of reformation as in 14 radiant carbon technique in addition to the intensive field work which enables to extract the river network of Al-Rimah in its lower sector. it proved its old floods and its dangerous on the neighboring housing areas. It helped in revealing the time of the valley a activity and circumstances of its precipitation which it passed through. The study used the technique of red sign to discover the colorful characters for sand dunes in the area and in knowing its forms and morphology specifications. The study results lead that wadi Al-Rimah the lowest Al-Rimah valley has witnessed a period of activity during the beginning of Alioto seen before 9450 year b.c. The study results lead to the adjusting of the hydrology network of the valley. It also leads to the distinguishing of a lot of positions, shapes, neighbors which are in highly danger position. The lugsail or should re consider it and shoed stop anyone to build or own in these areas which belong s to the stream of wadi Al-Rimah flood.